Critical Assessment of Islamic Educational Curriculum: Fostering Interfaith Tolerance through Sharia-Based Moral Pedagogy - Taufiq Taufiq; Kardina Engelina Siregar; Mohammed Dawood Ansari (International Forum of Researchers and Lecturers, 2024)
Islamic education holds a strategic position in shaping students’ moral character and social attitudes within multicultural societies. However, Islamic educational curricula are frequently perceived as prioritizing normative-textual transmission and doctrinal compliance, leaving limited room for interfaith dialogue and the cultivation of inclusive dispositions. This study critically assesses Islamic educational curriculum orientations and examines how sharia-based moral pedagogy can foster interfaith tolerance among students. The study also responds to the limited empirical linkage between sharia moral education and measurable developments in tolerance, inclusivity, and dialogic competence in Islamic schooling contexts. Using a qualitative design with descriptive-critical analysis, the research draws on curriculum document analysis and classroom observations across several Islamic educational institutions. Data are analyzed thematically to identify how three key curricular dimensions-akhlak (ethical conduct), maqāṣid al-sharī‘ah (higher moral objectives), and Islamic civilization history-are embedded and enacted in teaching practices, as well as how these elements shape students’ attitudes toward religious difference. The results indicate that akhlak-centered learning supports empathy, mutual respect, and non-discriminatory behavior by framing morality as lived practice rather than abstract instruction. Integrating maqāṣid al-sharī‘ah strengthens students’ inclusive orientation by emphasizing public good, justice, and human dignity as guiding principles for social relations. Additionally, teaching Islamic civilization history-especially narratives of coexistence-enhances students’ awareness of interfaith engagement and positions dialogue as compatible with Islamic identity. A comparative analysis suggests that sharia-based moral pedagogy is more effective than normative-textual curricula in building tolerant and inclusive student dispositions, mainly because it enables reflective learning, contextual moral reasoning, and dialogic interaction.